Assessment of Land Use Impacts on the Natural Environment. Part 1: An Analytical Framework for Pure Land Occupation and Land Use Change (8 pp) - Scholz, Roland (The international journal of life cycle assessment, 2007)
-: Part 1: An analytical framework for pure land occupation and land use changePart 2: Generic characterization factors for local species diversity in Central Europe -: Preamble. This series of two papers is based on a PhD thesis (Koellner 2003) and develops a method on how to assess land use impacts on biodiversity in the framework of LCA. Part 1 further expands the analytical framework of the thesis for pure land occupation and land use change. Part 2 rests on a much richer database compared to the thesis in order to quantify generic characterization factors for local species' richness. -: AbstractGoal, Scope and Background. In the framework of LCA, land use is broadly accepted as an impact category. However, the methodology for the assessment of damages on the natural environment was and still is the subject of discussion. The main objective of this paper is to contribute to that discussion by providing a consistent methodological framework for the assessment of land occupation and transformation. METHODS: We clarify the context of LCA relevant land use decisions. Based on that, we develop a formal model with damage functions and generic characterization factors for quantifying damages on ecosystems from land occupation and land transformation. The characterization factor for land occupation and land use change is labeled Ecosystem Damage Potential (EDP). We analytically address the substitutability of area and time occupied in order to produce a constant output. RESULTS: Based on the proposed method, it is possible to calculate the damages from complex series of land transformation, land occupation, and land restoration. A main feature of the method is that land transformation is assessed based on a factual or virtual, restoration time. This means that the damage of land transformation is largest for land use types which are difficult to restore and need extremely long to develop (e.g. thousand of years and more for primary forest and peatbog). In addition, we could show that area and time of occupation are not substitutable. The more severe the damage potential of a specific land use type is, the better it is to minimize the area and maximize the duration of occupation. DISCUSSION: An approach for the assessment of pure land occupation and land use change was developed in this paper, which is not geographically referenced. Developing geographically-referenced land use inventories and impact assessment methods can increase their accuracy. The information cost to provide geographically referenced data on land use for practical LCA applications, however, would increase enormously. CONCLUSIONS: An impact assessment method for land use with generic characterization factors improves the basis for decision-making in industry and other organizations. It can best be applied to marginal land use decisions; that is, to decisions in which the consequences are so small that the quality or quantity of environmental parameters of a region is not noticeably altered. RECOMMENDATIONS AND PERSPECTIVE: . One main problem to address is the development of reliable generic characterization factors, which express the ecosystem damage potential of specific land use types. The characterization factors should be developed on an empirical basis, which allow decision makers to get access to knowledge from environmental sciences in a very condensed form. In order to support decisions on distinct land use projects, methods should be developed, which allow accomplishing a generic assessment with site-dependent assessments.